AN IMPACT ASSESSMENT ON A FOOD PROCESSING TECHNOLOGY PROJECT IN CALINOG, ILOILO, PHILIPPINES - B. Moreno, Raymund; L. Caballero, Jovie (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This study was conducted to assess the impact of a food processing technology project which was implemented at Brgy. Simsiman, Calinog, Iloilo according to general and specific category classifications. This was done in order to determine the segmented results of the project and what the intervention approaches are achieving. A 4-part method for data collection and assessments were utilized, namely: 1. Respondents’ profiling survey; 2. Project status monitoring; 3. Impact assessment survey; and 4. Conduction of a focus group discussion. Established data collection and analysis procedures were employed to get accurate results. The results show that over-all, the project has a “high impact” change” (Md= 3.53). With the specific category classifications, it’s either “high impact” or “moderate impact” - Age:  less than 40 (Md=3.53); 40 and over (Md=3.38). With regard to family size, 5-member families (Md=3.64); 7-member families (Md=3.52); and 2-member families (Md=3.07). For educational attainment: finished elementary level (Md=3.54); high school level/ graduate (Md=3.53); and reached or finished college education (Md=3.07). Therefore, it can be concluded that the objectives were successfully obtained. Further, the classification of the categories used may not have a direct correlation to the impact of the study to them but is a great tool to draw insights and inferences. It is hereby recommended that more parallel studies focusing on other aspects and sub-categories be conducted and should utilize the results and discussions herein as a baseline data for a possible complementing result.